1984
DOI: 10.1093/jac/13.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind placebo-controlled trial of erythromycin in the treatment of clinical campylobacter infection

Abstract: In a double-blind placebo-controlled trial in patients hospitalized with campylobacter infection, erythromycin lessened pain and curtailed the carriage state but otherwise did not alter the natural course of the illness, which proved to be a short-lived, self-limiting one, even in this selected group of hospitalized patients; the majority had become asymptomatic by the time of the bacteriological diagnosis. The rarity of bacteraemia is highlighted by the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…In most immunocompetent individuals, campylobacteriosis is a self-limiting disease, and treatment with antimicrobials reduces the period of fecal shedding but does not have a large impact on the duration of disease symptoms (4,105,180). However, when given early, some clinical benefit has been observed (126,147).…”
Section: Pathology and Pathophysiology Of Campylobacter Infectionmentioning
confidence: 99%
“…In most immunocompetent individuals, campylobacteriosis is a self-limiting disease, and treatment with antimicrobials reduces the period of fecal shedding but does not have a large impact on the duration of disease symptoms (4,105,180). However, when given early, some clinical benefit has been observed (126,147).…”
Section: Pathology and Pathophysiology Of Campylobacter Infectionmentioning
confidence: 99%
“…Although the disease is generally self-limiting, early antibiotic treatment may alleviate the discomfort and pain and reduce the excretion period (Mandal & Ellis, 1983). Unfortunately, the isolation of C. jejuni from faeces requires a 48 h incubation time, in the presence of selective antibiotics, under demanding microaerophilic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of clinical trials performed in adults and children, erythromycin has not been shown to significantly alter the clinical course of Campylobacter infection (1,12,13,15,16,20). Results of one study, however, found that when Peruvian children with bloody diarrhea due to Campylobacter isolates were treated early in the course of illness with erythromycin, they improved earlier than children given placebo (21).…”
mentioning
confidence: 99%